Find the remainder when ∑ k = 1 4 0 ( k 3 − 1 ) k ! divided by 97
please submit yours solutioon :D
this problems originally from OMITS 2015
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sir, it seems that mine was 1000 times bigger than your solution! This solution is nice one.
How did you come up with that way of writing k 3 − 1 ?
Log in to reply
The first thing that came into mind was telescoping series, because I'm not going to calculate the remainder of 39 different numbers. So I tried to state the expression in terms of a n + 1 − a n
This is exactly how I did it, and I was wondering if there was an easier way to simplify the last step as well.
I didn't understand the last step . Can you please explain ?
Log in to reply
I want to evaluate 4 1 ! m o d 9 7 . In order to reduce the calculations, I paired the first term and last term together, second term and second last term together, and so on.
For example 1 × 4 1 ≡ 4 1 , 2 × 4 0 ≡ 8 0 ≡ − 1 7 , 3 × 3 9 ≡ 3 0 , 4 × 3 8 ≡ 7 6 × 2 ≡ − 2 1 × 2 ≡ − 4 2 , … , 2 5 × 2 7 ≡ 2 6 2 − 1 ≡ − 3 . Then combine all of them together, and repeat the process to get a single value, which is still very tedious to work with....
Log in to reply
However, I can reduce to two possible answers, which are 6 , 9 5 . But only one of them is right.
Here's my work, less tedious, but still...
By Wilson's Theorem
9 6 ! m o d 9 7 4 1 ! ( 4 2 × 4 3 × … × 9 6 ) 4 1 ! ( − 1 × − 2 × … × − 5 5 ) 4 1 ! × 5 5 ! 4 1 ! 2 ( 4 2 × 4 3 × … × 5 5 ) 4 1 ! 2 × 1 1 4 1 ! 2 ≡ ≡ ≡ ≡ ≡ ≡ ≡ ≡ 1 1 − 1 − 1 1 1 , still plenty of work 1 5 3 , by Extended Euclidean Algorithm 5 3 + 9 7 ( 4 ) ≡ 2 1 2
Which implies 4 1 ! ≡ 2 1 , − 2 1 , but only one of these values are right.
So that's quite tedious . I thought you were able to do simplification quite easily . Anyway, Thank you very much
Problem Loading...
Note Loading...
Set Loading...
Note that k 3 − 1 = ( k + 1 ) ( k + 2 ) ( k + 3 ) − 6 ( k + 2 ) ( k + 1 ) + 7 ( k + 1 ) − 2
Thus, we have
( k 3 − 1 ) k !
= ( k + 3 ) ! − 6 ( k + 2 ) ! + 7 ( k + 1 ) ! − 2 k !
= [ ( k + 3 ) ! − ( k + 2 ) ! ] − 5 [ ( k + 2 ) ! − ( k + 1 ) ! ] + 2 [ ( k + 1 ) ! − k ! ]
This is a Telescoping Series, which gives the value
( 4 3 ! − 3 ! ) − 5 ( 4 2 ! − 2 ! ) + 2 ( 4 1 ! − 1 ! ) = = = 4 3 ! − 5 ( 4 2 ! ) + 2 ( 4 1 ! ) + 2 4 1 ! ( 2 − 5 ∗ 4 2 + 4 3 ∗ 4 2 ) + 2 4 1 ! ( 1 6 ( 9 7 ) + 4 6 ) + 2
Consider Modulo 9 7
≡ 4 6 ( 4 1 ! ) + 2 ≡ 6
The penultimate step involved plenty of tedious arithmetic calculation by pairing as such
4 1 ! = ( 1 × 4 1 ) × ( 2 × 4 0 ) × ( 3 × 3 9 ) × … × ( 2 5 × 2 7 ) × 2 6
I hope there's a simpler solution than mine.